Design of a Mobile Microrobot Based on Standing and Travelling Waves. (30th April 2013) - Bansevicius, Ramutis; Drukteiniene, Asta; Kulvietis, Genadijus; Tumasoniene, Inga
The design of a mobile microrobot based on standing and travelling waves is proposed and analysed in this paper. Numerical modelling based on the finite element method is performed to find the resonant frequencies and modal shapes of a microrobot, and to calculate the trajectories of the upper points' movements under an excitation scheme. Geometric Path-Planning Algorithms for a piezoelectric hemispheric microrobot and an experimental study of this are presented in this paper.